The neuroscience of spirituality, religion, and mental health: A systematic review and synthesis. (December 2022) - Rosmarin, David H.; Kaufman, Caroline C.; Ford, Stephanie Friree; Keshava, Poorvi; Drury, Mia; Minns, Sean; Marmarosh, Cheri; Chowdhury, Avijit; Sacchet, Matthew D.
Abstract: Prior research highlights the importance of spirituality/religion (S/R) as it relates to several aspects of mental health and clinical interventions. This research has been expanded to include the concurrent examination of neurobiological correlates of S/R to elucidate potential biological mechanisms. However, the majority of neurobiological research on S/R has neglected mental health, and the relationship across all three of these domains (S/R, mental health, and neurobiology) remains unclear. This study systematically reviewed research concurrently examining S/R, mental health, and neurobiology, and rated the methodological quality of included studies. Eighteen identified studies were then included in an integrated literature review and discussion, regarding the neurobiological correlates of S/R as it pertains to depression, anxiety, alcohol/substance misuse, and psychosis. The majority of studies demonstrated moderate to high methodological quality. Findings highlight the need for additional studies in this area as well as research that includes validated assessment of S/R.